2011
DOI: 10.1111/j.1537-2995.2011.03432.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasovagal reactions in whole blood donors at three REDS‐II blood centers in Brazil

Abstract: Background In Brazil little is known about adverse reactions during donation and the donor characteristics that may be associated with such events. Donors are offered snacks and fluids prior to donating and are required to consume a light meal after donation. For these reasons the frequency of reactions may be different than those observed in other countries. Methods A cross-sectional study was conducted of eligible whole blood donors at three large blood centers located in Brazil between July 2007 and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 37 publications
2
26
0
2
Order By: Relevance
“…The incidence in this study was 1.1% in a one year study period, which was less than studies conducted in three large blood centers that reported a total incidence of 16,129/724,861(2.3%) [14]. The American Red Cross has reported an incidence of vasovagal reactions among 435 cases per 10,000 blood donations [15].…”
Section: Resultsmentioning
confidence: 68%
“…The incidence in this study was 1.1% in a one year study period, which was less than studies conducted in three large blood centers that reported a total incidence of 16,129/724,861(2.3%) [14]. The American Red Cross has reported an incidence of vasovagal reactions among 435 cases per 10,000 blood donations [15].…”
Section: Resultsmentioning
confidence: 68%
“…Bermudez et al (2013) complementam que a frequência de eventos adversos na doação sanguínea é de aproximados 5%, sendo subdivididas em três categorias conforme sua manifestação, podendo ser relacionadas a sintomas vasovagais, referentes a procedimentos de punção e, por conseguinte, a métodos que necessitem da aplicação de anticoagulantes, como nos casos de aférese. Goncalez et al (2012) Ainda, quando fornecida a lista de doenças verificadas observou-se que maior nível de conhecimento que os participantes dispunham era a respeito do HIV, seguido pela doença de Chagas, sífilis e hepatite C e B (57,8%). Para Carvalho (2013), o Brasil é um dos países considerados com cobertura sorológica universal, o risco de transmissão por transfusão sanguínea está correlacionado com casos na falha da sensibilidade dos testes sorológicos e relativas falhas clericais, entretanto há alguns anos os testes apresentam sensibilidade superior a 99,5%.…”
Section: ____________________________________________________________unclassified
“…Gonçalez et al also reviewed 700,000 whole blood donations to assess adverse reactions among blood donors and observed an overall reaction rate of 2.2% 7 . However, the rates were very different in each center: 53, 290, and 381 per 10,000 donations in Recife, São Paulo, and Belo Horizonte, respectively.…”
Section: Database Analysesmentioning
confidence: 99%